2001
DOI: 10.1054/bjoc.2001.1926
|View full text |Cite
|
Sign up to set email alerts
|

HPV presence precedes abnormal cytology in women developing cervical cancer and signals false negative smears

Abstract: In a retrospective case–control study, we investigated high-risk HPV DNA presence by general primer GP5+/6+ PCR in the last normal cervical smear in the patient archives (i.e. baseline smear) of 57 women who later developed cervical cancer. Also, normal cervical smears of 114 age-matched control women were analysed. High-risk HPV DNA was detected in 37 of the 57 (65%) baseline smears of the case women, and 7 (6%) of 114 smears of the control women (OR 28, 95% Cl 11–72). The HPV positive subsequent smears and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
81
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 16 publications
(15 reference statements)
7
81
1
2
Order By: Relevance
“…To solve the uncertainty on the confounding of regressive CIN III lesions, this prospective analysis with CIN III as end point should be accompanied by archival studies, in which retrospectively the HPV status of smears preceding a diagnosis of cervical cancer, is assessed. Zielinski et al (2001) concluded in a retrospective study of 57 women with invasive cervical cancer that the detectable preclinical stage could be prolonged by at least 2 years by adding HPV testing, which corroborates our results. This type of study, however, is susceptible to confounding biases such as selection and length time bias, which may result in an underestimation of the extension of the detectable preclinical stage as cervical cancers found after participation in a screening programme may be selective towards fast-growing cancers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To solve the uncertainty on the confounding of regressive CIN III lesions, this prospective analysis with CIN III as end point should be accompanied by archival studies, in which retrospectively the HPV status of smears preceding a diagnosis of cervical cancer, is assessed. Zielinski et al (2001) concluded in a retrospective study of 57 women with invasive cervical cancer that the detectable preclinical stage could be prolonged by at least 2 years by adding HPV testing, which corroborates our results. This type of study, however, is susceptible to confounding biases such as selection and length time bias, which may result in an underestimation of the extension of the detectable preclinical stage as cervical cancers found after participation in a screening programme may be selective towards fast-growing cancers.…”
Section: Discussionsupporting
confidence: 90%
“…For Pap smear screening, the preclinical duration was the combined duration of CIN and microinvasive cervical cancer, a period estimated at 15 years on average (Gustafsson and Adami, 1989;Habbema, 1991, 1995;van Oortmarssen et al, 1992;Zielinski et al, 2001). Consequently, adding the HPV test to primary screening leads to duration of the detectable preclinical stage of almost 20 years in women aged 34 -54 years.…”
Section: Discussionmentioning
confidence: 99%
“…7,14,19 Triage with HPV-testing as an adjunct to cytology has been proposed for women with minimal cytological changes. 15,17,23 Several studies have used different classifications of mildly abnormal cytology.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Consequently, HPV-testing may play an important role in clinical practice, i.e., in triage of women with BMD cytology, as an adjunct to cytology in primary screening and in posttreatment protocols. [15][16][17] The prevalence of hrHPV in women with BMD smears is about 35% 18,19 and it is likely that hrHPV negative BMD women are not at risk for development of high-grade CIN lesions or carcinoma. Hence, triage with hrHPV testing may improve the selection of women at risk for development of cervical cancer and consequently the management of women with BMD smears.…”
mentioning
confidence: 99%
See 1 more Smart Citation